ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAAN PELANGGAN (STUDI KASUS PENGURUSAN SURAT IZIN USAHA PERDAGANGAN DI KANTOR PELAYANAN PERIJINAN TERPADU KOTA PALEMBANG) - Novia Kencana; Muhammad Josyaranda Akbar; Rendy Sueztra Canaldhy (Jurnal Pemerintahan dan Politik, 2019)
Quality of service is a response to the applicant on the level of service that is hosted by the Office of Integrated Licensing Services (KPPT) of Palembang as statements feeling of care received at the time taking care of business license letter (SIUP). This study aimed to analyze the dimensions of service quality ie reliability, responsiveness, assurance, empathy and tangible based on observations and interviews delivered by employees and customers at the time taking care of Trade Business License (License) in the Integrated Licensing Services Office (KPPT) of Palembang. The method used is descriptive method with qualitative approach. Observations and interviews with respondents on 5 indicators show that the physical evidence (Tangibles) from the comfort of the service is still less than satisfactory, reliability (Reliability) of the cost and timeliness of the necessary permits are still not satisfied, responsiveness (Responsiveness) from providing easily understandable information still not satisfied, the guarantee (assurance) of the attitudes and actions of officers as well as friendliness towards customers still lacking. The last indicator is empathy (Empathy) measured from providing delightful service to customers can be categorized own good, but because of the high public expectations on the performance of the service of this dimension, then this condition gives effects on the service user is not satisfied with the services received.Keywords : quality of service, Business license letter (SIUP),integrated license service offices (KPPT)